2006
DOI: 10.1007/bf03167962
|View full text |Cite
|
Sign up to set email alerts
|

The experiences and attitudes of general practitioners and hospital staff towards prehospital thrombolysis in a rural community

Abstract: Pre-hospital thrombolysis programmes must be continuously monitored and evaluated to identify important factors that may prevent wider use of thrombolytic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Early evidence suggested that the initiation of traffic laws involving demerit or penalty points dramatically reduced total number of fatalities on the roads in some countries [ 4 , 5 ]. However, this benefit was not sustained [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early evidence suggested that the initiation of traffic laws involving demerit or penalty points dramatically reduced total number of fatalities on the roads in some countries [ 4 , 5 ]. However, this benefit was not sustained [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%